2008
DOI: 10.1111/j.1600-0625.2008.00712_1.x
|View full text |Cite
|
Sign up to set email alerts
|

What causes hidradenitis suppurativa?

Abstract: Hidradenitis suppurativa (HS)--a rather common, very chronic and debilitating inflammatory skin appendage disorder with a notoriously underestimated burden of disease--has long been a playground for the high priests of nomenclature: Ask a bunch of eminent dermatologists and skin pathologists to publicly share their thoughts on what causes HS, and they will soon get entrenched in a heated debate on whether this historical term is a despicable misnomer. Fortunately, the recently founded Hidradenitis Suppurativa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
83
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(97 citation statements)
references
References 9 publications
1
83
0
2
Order By: Relevance
“…The disease is characterized by painful, inflammatory nodules or boils that may progress to abscesses, sinus tract formation and scarring 2, 3. Although the aetiology of HS is largely unknown, it is likely that multiple factors contribute to the development of the disease 4…”
Section: Introductionmentioning
confidence: 99%
“…The disease is characterized by painful, inflammatory nodules or boils that may progress to abscesses, sinus tract formation and scarring 2, 3. Although the aetiology of HS is largely unknown, it is likely that multiple factors contribute to the development of the disease 4…”
Section: Introductionmentioning
confidence: 99%
“…It has a significant impact on the patients’ quality of life [2, 3]. The exact cause of HS remains unclear [4]. Histopathological studies have suggested occlusion of the follicular infundibulum as an important factor [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…HS is currently thought of as being a sterile inflammation, but bacteria are suspected of playing a role in the disease process, although not that of a simple infection. It is speculated that bacteria may play a part through immune-mediated mechanisms of inflammation in association with a dysregulated immune response in the hair follicles [4]. Antibiotic therapy is however widely used and mentioned in all textbooks of dermatology as a prominent form of treatment for HS.…”
Section: Introductionmentioning
confidence: 99%
“…It is rare in children. While its aetiology remains unknown, the organs involved and the pathogenesis of the disease are thought to be well understood [2]. Several studies have identified the hair follicle as the core element of hidradenitis, prompting some authors to suggest that the disease be renamed acne inversa, although substantial differences exist between the 2 diseases [1,3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%